MORPHOLOGICAL AND MORPHOMETRIC STUDIES ON THE PELVIC GIRDLE OF CHINESE GOOSE (ANSER CYGNOIDES) - O.R. Sathyamoorthy; R. Richard Chruchil; S. Dhamotharan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The pelvic girdle of Chinese goose was a large, elongated bone, narrow cranially (3.0 cm) and wide (8.0 cm) caudally. It consisted of two os coxae, each of which was made up of an ilium, an ischium and a pubis. The ilium of the Chinese goose was the largest and longest (14 cm) bone of the os coxae. The pre-acetabular part of the ilium was 6.80 cm long and 2.0 cm wide. The post-acetabular part of ilium was 7.2 cm long. The ilioneural canal was slightly broad in front and narrow caudally. The pelvic surface of ilium showed six openings on either side of the bodies of the lumbosacral mass. The ischiatic foramen was 3.60 cm long and 1.20 cm wide. The ischium was triangular in shape and 7.50 cm long. The caudal border of the pelvis was wide (7.50 cm) and showed a deep notch. The pubis was long (12.0cm), thin, bent rod-like bone, projected well beyond the caudal border of the os coxae and bent medially. The pectineal process was short and rounded. Pneumatic foramina were absent in the os coxae of the Chinese goose. The acetabulum was large and formed by all the three bones. The anti-trochanter was quadrilateral in shape and prominent.